Gonadosomatic index-based size at first sexual maturity of male and female Amblygaster clupeoides (Bleeker, 1849) (Clupeidae) on the east coast of the Malaysian peninsular - Rahman, Mohammad Mustafizur (Blackwell Publishing Ltd, 2017)
Size at first sexual maturity and condition of Amblygaster clupeoides were determined in a population at the Malaysian east coast. A total of 887 specimens were collected from commercial fishing vessels between March and November 2012. A random sample was taken each time to avoid bias in the cohort sampling. Size at first sexual maturity was determined by the relationship between the total length and gonadosomatic index (GSI). Similarly, the relationship between the condition factor and GSI was applied to determine the condition at first sexual maturity. The sex ratio was close to 1:1. The total length at first sexual maturity of both males and females were at around 18 cm. Males with a GSI of ≥3.2% and females with a GSI of ≥6.5% were mature, having condition factors of ≥0.90 and ≥0.93, respectively. Based on these results the minimum permissible capture size was identified. This study establishes a strong need for regular and continued monitoring of the changes in fish size at first sexual maturity.